Should There Be A Second Chance for Ex-ISIS Indonesians? - Kamil, Rizqan; Fauzi, Muhammad Fahmi Basyhah (Journal of International and Local Studies, 2023)
The year of 2019 was hard on Islamic State in Iraq and Syria (ISIS), they lost their main territories and suffer from collapsing until finally lost their leader, al-Baghdadi, by US attack late October 2019. The situation led to the escape of thousands of their ex-members that currently stranded in several different refugee camps in Syria, among the thousands several hundred are Indonesian citizens. On February 11th 2020, the Indonesian government decided to not taking back all 689 Indonesian citizens that previously involved in the mentioned terrorist organization. This decision was taken under the pretext of preventing radical ideas to develop in Indonesia’s soil and ensuring the safety of Indonesian people from the threats of terrorism. Within this paper, we would like to challenge Indonesia’s decision by assessing the situation through the concept of international law and international security. According to the Universal Declaration of Human Rights and 1961 Convention on Reduction of Statelessness, every country should prevent its citizens from being stateless, thus Indonesia is in no position to reject its citizens and must assist them to get back to their country. Using the notion of international security, it is theoretically more beneficial for Indonesia to take their citizens back, rejection may lead to more dangerous retaliation by the abandoned citizens and could possibly cause bigger harm in their current state. This paper will try to offer alternative viewpoints to the current Indonesia’s policy.